Rethinking Conservative Treatment of Humeral Diaphyseal Fractures in Elderly Patients With Dementia. Issue 12 (December 2022) - Eisenberg, Gilad; Otremski, Hila; Segev, Elad; Sherman, Hagai; Steinberg, Ely L.; Tordjman, Daniel; Pritsch, Tamir; Rosenblatt, Yishai; Atlan, Franck
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To assess outcomes and complications of conservatively managed humeral diaphyseal fractures in elderly patients, with an emphasis on the subgroup diagnosed with dementia. Design: Retrospective. Setting: Upper extremity surgery unit at an academic Level I trauma center. Patients/Participants: Consecutive patients 65 years of age and older who were managed conservatively for humeral diaphyseal fractures between 2007 and 2015. Intervention: Conservatively managed humeral diaphyseal fractures. Main Outcome Measurements: Complications and radiographic outcomes. Results: One-hundred twenty-four patients who were conservatively managed for humeral diaphyseal fractures were identified. Their mean age was 77 (65–92) years, 36 (30%) of them were male and 88 (70%) were female. Fifty-seven (46%) patients experienced complications associated with their treatment, and 33 (27%) patients were eventually treated surgically. Seventeen (14%) patients were diagnosed with dementia. This subgroup had 64% fracture-related complications, and all of them were operated ( P -value <0.01 compared with age-matched patients among the other 107 participants in the study). Conclusion: Conservative management of humeral diaphyseal fractures seems to be associated with greater morbidity in elderly patients, especially in those diagnosed with dementia. Therefore, early surgical treatment should be considered. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.